PENGARUH LUAS LAHAN, TENAGA KERJA DAN IRIGASI TERHADAP PRODUKSI PADI DI PROVINSI ACEH - Manda Fitri; murtala murtala (LPPM Universitas Malikussaleh – Indonesia, 2021)
This study aims to analyze the effect of land area, labor and irrigation area on rice production in Aceh province 1998-2017. This researchmodel uses multiple linear regression. Theresults of the study partiallyland area (X1) affects Rice Production in Aceh, Labor (X2) affects RiceProductionin Aceh Province, Irrigation (X3). Simultaneously the area ofland, labor and irrigation area affect rice production in Aceh Province.Keywords:land area, labor, irrigation area,rice production